Heat shock proteins and their role in human diseases - Tóth, Melinda Erzsébet; Gombos, Imre; Sántha, Miklós (Acta Biologica Szegediensis, 2015)
Elevated expression of heat shock proteins (HSPs) has been demonstrated following various forms of stress, such as heat, heavy metal or ethanol treatment, hypoxia, ischemia, and they are also upregulated in several diseases and infections, as their most important function is to protect cells from the harmful effects of stress. As molecular chaperones they regulate the biosynthesis, folding/unfolding, transport and assembly of cellular proteins. Following cellular stress, they protect uncorrectly folded proteins against aggregation, facilitate the refolding of misfolded proteins. In addition, these proteins also can assist in the proteasomal degradation of peptides that cannot be refolded. They also have crucial role in membrane quality control by binding to lipid rafts maintaining the membrane stability during stress conditions. Moreover, HSPs can inhibit certain steps of the apoptotic pathway and they also can decrease the damaging effect of oxidative stress. These properties enable them to have protective effects in different pathological conditions. Here, we summarize our current view on the role of HSPs in human diseases like myocardial infarction, ischemic stroke, different neurodegenerative disorders, diabetes or cancer.